Studies on thermal behavior, moisture absorption, and biodegradability of ginger spent incorporated polyurethane green composites. Issue 10 (30th October 2014) - Chethana, M.; Prashantha, Kalappa; Siddaramaiah
ABSTRACT Ecological concern on accumulation of neutraceutical industrial waste material and the demands for newer composite materials have promoted extensive research on utilizing industrial wastes materials. Therefore, in the present study finely powdered ginger spent (GS), filled polyurethane (PU) green composites with varying amount viz., 0, 2.5, 5, 7.5, and 10 wt % of GS have been fabricated. The prepared PU/GS green composites have been characterized for their mechanical properties, density and void content. Interaction between filler and matrix has been confirmed from Fourier transform infrared spectroscopy studies. Moisture absorption and desorption studies have been performed at different relative humidity (RH). The moisture absorption and desorption studies, shows that as the hydrophilic GS content increases in the matrix the RH also increases. Water uptake behavior of PU/GS were measured in different chemical environments such as 5% sodium chloride solution, cold water at different temperature and in hydrochloric acid solution. The water uptake values increases as increase in GS concentration. Equilibrium water content, diffusivity and equilibrium time taken for all PU/GS composites have been investigated. Biodegradation studies reveals that as the GS content increases the weight loss also increases. Thermal properties have been performed using differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). From DSC and DMA thermograms it is revealed that increase in Tg with increase in GS content. RH and contact angle measurement have been performed to understand the hydrophilic nature of the prepared composite. The morphological behavior of composites has been studied using scanning electron microscopy. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41614.